2007
DOI: 10.1016/j.jadohealth.2006.11.137
|View full text |Cite
|
Sign up to set email alerts
|

Aggression in Adolescent Dating Relationships: Prevalence, Justification, and Health Consequences

Abstract: These differential tendencies of aggression typology for men and women help clinicians to develop preventive interventions for every age, with the aim of diminishing their continuity in future relationships.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
144
5
78

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 236 publications
(254 citation statements)
references
References 31 publications
27
144
5
78
Order By: Relevance
“…Although there were no broad level gender differences in the present study, as stated previously, contradicting results have emerged in the field. Some research suggests that women tend to be the perpetrators in verbal and physical aggression (Munoz-Rivas et al, 2007), yet women also report being victimized more often than men (Marquart, Nannini, Edwards, Stanley, & Wayman, 2007). This study provides support that men and women equally report abuse and their mode of communication technology may only differ marginally.…”
Section: Discussionmentioning
confidence: 99%
“…Although there were no broad level gender differences in the present study, as stated previously, contradicting results have emerged in the field. Some research suggests that women tend to be the perpetrators in verbal and physical aggression (Munoz-Rivas et al, 2007), yet women also report being victimized more often than men (Marquart, Nannini, Edwards, Stanley, & Wayman, 2007). This study provides support that men and women equally report abuse and their mode of communication technology may only differ marginally.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that more females than males reported physical dating violence perpetration did not surprise us, however, as more than 15 prior studies have also found female adolescents to report more dating violence perpetration than males. 24,34,36,[57][58][59][60][61][62][63][64][65][66][67][68][69] As stated in the Introduction, it is our view that the prevention of "common" dating violence is important and merits research attention because of the potential for even non-severe physical violence to result in harm, and because it has the potential to normalize the use of physical assault in all types of interpersonal relationships.…”
Section: Limitationsmentioning
confidence: 99%
“…Although some studies have already been published in both countries (Menesini & Nocentini, 2008Mun˜oz-Rivas, Gran˜a, O'Leary, & Gonza´lez, 2007a, 2007b, none presents a direct comparison between the two countries. A previous study showed the reciprocal involvement of partners in both roles of perpetrator and victim in Italy (Menesini & Nocentini, 2008), but no specific investigation has yet been conducted on this profile among Spanish adolescents.…”
Section: Cross-cultural Considerationsmentioning
confidence: 99%